The Invisible Wounds of War: Trauma, Identity Loss, and Social Disintegration Among Bajaur’s Internally Displaced Persons (2008–2015): https://doi.org/10.55966/assaj.2025.4.1.062 - Khubaib Ali; Nasrullah; Sheema Rahman (`, 2025)
The paper addresses the psychological and emotional effects of forced migration on the internally displaced persons (IDPs) in Bajaur, a tribal district in former Federally Administered Tribal Areas (FATA) in Pakistan, which witnessed forced migration between 2008 to 2015 because of military operation. With a qualitative framework based on narrative type inquiry and thematic analysis, the study looks into the multidimensional issues that these societies experience, more so on trauma, loss of identity, and social melting. Exploring the results on the basis of field interviews, case studies, and documentary analysis, it can be concluded that most IDPs display the symptoms of anxiety, depression, and post-traumatic stress disorder (PTSD). The mandatory excursion was not only deprived of people of homes but, also, cultural integrity, sex roles and tribal integration proved to be shattered, thus causing confusion of identity and cultural dichotomy. The camps and the receiving communities failed to offer psychosocial support required to aid in recovery, but mostly offered a prolonged state of dependency, instability and normlessness. However, the research is also based on the Trauma Theory, Social Identity Theory, and the notion of anomie by Durkheim, which provides a duality of theoretical perspective and views on the affliction of the person, as well as the group. It further combines Forced Migration theory with the Resilience theory in evaluating coping strategies and survival mechanism. Policy implications make it clear that even procedural trauma-informed rehabilitation systems, ethnically aware education, and identity recovery programs are urgently needed in such post-violence zones as Bajaur. The study is also one of the few studies focusing on localized IDPs in Pakistan and further calls upon the need to adopt a humanistic and perspective that transcends physical settlement, and further more focuses on the internal wounds of a war, the invisible wounds of war or what the IDPs call it the feeling of emptiness. Keywords: Bajaur Agency, Trauma, Identity Loss, Displacement, Social Fragmentation, Mental Health, 2008–2015